2019
DOI: 10.3390/pharmaceutics12010007
|View full text |Cite
|
Sign up to set email alerts
|

Satureja montana L. Essential Oils: Chemical Profiles/Phytochemical Screening, Antimicrobial Activity and O/W NanoEmulsion Formulations

Abstract: Chemical fingerprints of four different Satureja montana L. essential oils (SEOs) were assayed by an untargeted metabolomics approach based on Fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometry (MS) coupled with either electrospray ionization or atmospheric pressure chemical ionization ion sources. Analysis and relative quantification of the non-polar volatile fraction were conducted by gas chromatography (GC) coupled to MS. FT-ICR MS confirmed significant differences in the polar metabolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 61 publications
5
43
0
2
Order By: Relevance
“…Oils, 2020;7(2): 22-34 Čopra-Janićijević et al DOI: 10.37929/nveo.743706 compilation on the essential oil diversity of species S. montana of various origins, it was found that chemotype A was the most prevalent among its essential oils studied to date. Thus, two isomeric monoterpene phenols -carvacrol and thymol along with two monoterpene hydrocarbons --terpinen and pcymene -appear as the main constituents in S. montana collected from different locations in Croatia as described by Milos et al (2001), Radonic & Milos (2003), Vidic et al (2009), Dunkić et al (2012), Ćavar et al (2013), as well as from Italy (Fraternale et al, 2007, Benelli et al, 2017, Caprioli et al 2019Albania (Ibrailu et al, 2011, Maccelli et al, 2020; Montenegro (Damjanović-Vratnica et al, 2011); Portugal (Santos et al, 2019); Serbia (Vidović et al, 2014), and Spain (Navarro-Rocha et al, 2020). Mediterranean and Sub Mediterranean bioclimates, moderate water stress, full flowering stage of the plant, and drying method can be critical factors that are able to enhance the percentage of carvacrol in the oil of the plants with chemotype A.…”
Section: Resultsmentioning
confidence: 97%
“…Oils, 2020;7(2): 22-34 Čopra-Janićijević et al DOI: 10.37929/nveo.743706 compilation on the essential oil diversity of species S. montana of various origins, it was found that chemotype A was the most prevalent among its essential oils studied to date. Thus, two isomeric monoterpene phenols -carvacrol and thymol along with two monoterpene hydrocarbons --terpinen and pcymene -appear as the main constituents in S. montana collected from different locations in Croatia as described by Milos et al (2001), Radonic & Milos (2003), Vidic et al (2009), Dunkić et al (2012), Ćavar et al (2013), as well as from Italy (Fraternale et al, 2007, Benelli et al, 2017, Caprioli et al 2019Albania (Ibrailu et al, 2011, Maccelli et al, 2020; Montenegro (Damjanović-Vratnica et al, 2011); Portugal (Santos et al, 2019); Serbia (Vidović et al, 2014), and Spain (Navarro-Rocha et al, 2020). Mediterranean and Sub Mediterranean bioclimates, moderate water stress, full flowering stage of the plant, and drying method can be critical factors that are able to enhance the percentage of carvacrol in the oil of the plants with chemotype A.…”
Section: Resultsmentioning
confidence: 97%
“…This method has widely demonstrated to be a powerful tool for characterizing the polar fraction of a variety of complex matrices such as foodstuff and essential oils. [29][30][31][32][33][34][35] Visualization of the so-obtained chemical profiles by van Krevelen diagrams affords a plain screening approach for the different Allium samples.…”
Section: Introductionmentioning
confidence: 99%
“…to attach, form intricate biofilms, and increase the resistance against any form of treatment [20]. Exploring plant-, polymer-, and nanotechnology-based therapeutic approaches rendered a plethora of promising results.Within the year 2019 alone, publications of medicinal plant-related research articles skyrocketed due to the huge interest of the scientific community to explore suitable therapeutic agents [21]. Targeting bacterial virulence factors like biofilm formation, quorum sensing, or motility instead of the viability is another interesting alternative in the current post-antibiotic-era [22].…”
mentioning
confidence: 99%
“…Within the year 2019 alone, publications of medicinal plant-related research articles skyrocketed due to the huge interest of the scientific community to explore suitable therapeutic agents [21]. Targeting bacterial virulence factors like biofilm formation, quorum sensing, or motility instead of the viability is another interesting alternative in the current post-antibiotic-era [22].…”
mentioning
confidence: 99%